Peran radioterapi lokoregional pada kasus karsinoma nasofaring dengan metastasis jauh: laporan serial kasus berbasis bukti - Mayangsari, Ika Dewi; Rahman, Muhammad Ade; Adham, Marlinda; Prajogi, Gregorius Ben; Cahyanur, Rahmat; Safitri, Eka Dian (Oto Rhino Laryngologica Indonesiana, 2023)
Background: Nasopharyngeal carcinoma (NPC) is a highly metastatic head and neck cancer primarilytreated with platinum-based chemotherapy. The oligometastasis hypothesis proposed by Hellman andWeichselbaum suggested that controlling the primary tumor through locoregional radiotherapy couldsignificantly improve prolonged disease-free survival. Purpose: To evaluate the effectiveness of combining locoregional radiotherapy with chemotherapy for metastatic NPC. Case series report: The first case involved a 57-year-old male with NPC at T4N3M1 (lungs) with partial response to chemotherapy, who then underwent concurrent chemoradiotherapy. However, his condition deteriorated after completing chemoradiation. The second case featured a 56-year-old male with NPC at T4N3M1 (liver), exhibiting partial response to chemotherapy and remaining at a stable condition after concurrent chemoradiotherapy. Method: Using specific keywords based on clinical questions in the PubMed, Cochrane, EBSCOhost, and Proquest databases. Inclusion criteria, exclusion criteria, and critical appraisal were carried out to find relevant studies. Result: Eleven articles were appraised critically based on the Oxford Centre for Evidence-based Medicine (CEBM) worksheet and include the validity, importance, and applicability in clinical scenarios. Conclusion: Metastatic NPC patients had better overall survival outcomes when treated with locoregional radiotherapy and systemic chemotherapy. Predictive factors influencing survival included oligometastasis, locoregional radiotherapy, chemotherapy response, lactate dehydrogenase, C-reactive protein, EBV DNA, total chemotherapy administration, Karnofsky performance score, number of metastatic lesions, and liver metastases. Platinum-based chemotherapy combined with locoregional radiotherapy could be considered as a management approach for cases of oligometastatic NPC.Keywords: nasopharyngeal carcinoma, chemotherapy, metastasis, overall survival, radiotherapy